Use of methylene blue in the prevention of recurrent intra-abdominal postoperative adhesions. Issue 1 (January 2018) - Neagoe, Octavian C.; Ionica, Mihaela; Mazilu, Octavian
Objective: To evaluate the efficacy of methylene blue in preventing recurrent symptomatic postoperative adhesions. Methods: Patients with a history of >2 surgeries for intra-abdominal adhesion-related complications were selected for this study. Adhesiolysis surgery was subsequently performed using administration of 1% methylene blue. The follow-up period was 28.5 ± 11.1 months. Results: Data were available from 20 patients (seven men and 13 women) whose mean ± SD age was 51.2 ± 11.4 years. Adhesions took longer to become symptomatic after the first abdominal surgery when the initial pathology was malignant compared with benign. However, the recurrence of adhesions after a previous adhesiolysis surgery had a similar time onset regardless of the initial disease. Following adhesiolysis surgery with methylene blue, the majority of patients did not present with symptoms associated with adhesion complications (i.e., chronic abdominal pain, bowel obstruction) for the length of the follow-up period. Conclusions: The use of methylene blue during adhesiolysis surgery appears to reduce the recurrence of adhesion-related symptoms, suggesting a beneficial effect in the prevention of adhesion formation.